Primary pulmonary Hodgkin's lymphoma mimicking rheumatoid arthritis‐associated organizing pneumonia: A case report - Kunyan Sun; Qing Yu; Jiaxin Zhou; Hong Zhang; Li Gao; Lin Nong; Mangju Wang; Chengli Que (Thoracic Cancer, 2021)
Abstract Primary pulmonary Hodgkin's lymphoma (PPHL) is an extremely rare disease. The nonspecific clinical and radiological features render the diagnosis a great challenge. Here, we present a case of PPHL mimicking rheumatoid arthritis‐associated organizing pneumonia.